Analisis Kuat Tekan dan Kuat Lentur Beton pada Struktur Perkerasan Kaku Akibat Penambahan Serat Baja - Nadya Shafira Salsabilla; Okky Hendra Hermawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Concrete is a material that has brittle properties, so it tends to be weak against tensile forces. As a result, concrete is prone to cracking when exposed to tensile loads or pressure that exceeds its capacity. To overcome this weakness, various innovations have been developed in the construction world. To overcome this problem, an innovation emerged, namely steel fiber concrete (concrete fiber steel) to strengthen the concrete structure and prevent early cracking. FS quality concrete can be a solution, it can withstand a compressive load of 400 kg / cm2. The purpose of this study was to determine the effect of adding steel fiber as a mixture of cement concrete pavement (Fs 45 concrete) and to determine the comparison of flexural strength and compressive strength values between normal concrete and concrete with the addition of steel fiber. The study used an experimental method with stages of physical testing of aggregate materials, making test objects and stages of flexural strength testing and compressive strength of normal concrete and steel fiber concrete aged 28 days. The steel fiber used used a fiber type with a diameter of 0.90 mm and a length of 60 mm. The average result of the flexural strength test of normal concrete aged 28 days was 4.65 Mpa. Meanwhile, concrete with the addition of steel fibers aged 28 days obtained an average flexural strength of 5.29 MPa. The average result of the normal concrete compressive strength test aged 28 days was 30.9 MPa, while concrete with the addition of steel fibers aged 28 days obtained an average concrete compressive strength of 33.4 MPa.